2008
DOI: 10.1248/jhs.54.482
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Endogenous Antioxidant and Ischemia-modified Albumin in Normolipidemic Acute Myocardial Infarction Patients

Abstract: Dyslipidemia appears to be a conventional risk factor for acute myocardial infarction (AMI). Several studies have reported decreased levels of antioxidants and increased levels of ischemia-modified albumin (IscMA) and lipid peroxides in dyslipidemic myocardial infarct patients. However, literature search reveals no reports of normolipidemic AMI patients with reference to antioxidants and IscMA studies. Therefore, this study determined the endogenous levels of antioxidants and IscMA in normolipidemic AMI patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…We found that the Serum levels of IMA were significantly higher in diabetic patients when compared with normal healthy non diabetic (p value = 0.003)this agree with previous study show that the IMA is a novel marker of tissue ischemia and accepted as a marker of oxidative stress in type 2 diabetes patients [15] and others study report that definite and precise mechanisms for IMA production in vivo, it appears to be related to the generation of reactive oxygen species (ROS) due to ischemia-reperfusion that modifies metal binding domains of albumin molecule [16]. Diabetic complications are due to various micro and macroangio-pathic events producing increased oxidative stress and decreased levels of antioxidants, which can lead to modification of albumin molecule of IMA than patients with less than 5 years duration of diabetes(long-stand diabetes) have a lower than the other one [18,17].…”
Section: Discussionsupporting
confidence: 88%
“…We found that the Serum levels of IMA were significantly higher in diabetic patients when compared with normal healthy non diabetic (p value = 0.003)this agree with previous study show that the IMA is a novel marker of tissue ischemia and accepted as a marker of oxidative stress in type 2 diabetes patients [15] and others study report that definite and precise mechanisms for IMA production in vivo, it appears to be related to the generation of reactive oxygen species (ROS) due to ischemia-reperfusion that modifies metal binding domains of albumin molecule [16]. Diabetic complications are due to various micro and macroangio-pathic events producing increased oxidative stress and decreased levels of antioxidants, which can lead to modification of albumin molecule of IMA than patients with less than 5 years duration of diabetes(long-stand diabetes) have a lower than the other one [18,17].…”
Section: Discussionsupporting
confidence: 88%
“…Kumar et al . [ 22 ] in their study ‘Oxidative stress, endogenous antioxidant, and IMA in normolipidemic acute myocardial infarction patients’ had shown decrease in endogenous antioxidants like uric acid, albumin, and bilirubin due to oxidative stress with a simultaneous increase in IMA. Albumin is the most abundant serum protein.…”
Section: Discussionmentioning
confidence: 99%
“…Principle ACB assay for determination of the level of IMA in serum is done by addition of a known amount of cobalt (II) to a serum specimen and measurement of the unbound cobalt (II) from the absorbance of the colored complex between dithiotreitol (DTT) and free cobalt by spectrophotometer which is indicative of the level of IMA [30]. Intensity of the colored complex varies inversely with the ACB.…”
Section: Acb Assay For Imamentioning
confidence: 99%